Liberalization of the Health Sector and Fulfillment of the Right to Health: How does international law respond to this condition? - Saraswati, Dhanny; Zulfa, Zaeda (International Law Discourse in Southeast Asia, 2023)
The liberalization of the health sector has become a contentious issue, raising questions about its impact on the fulfillment of the right to health. This paper explores the dynamics between health sector liberalization and the realization of the right to health within the framework of international law. It examines the principles and obligations enshrined in international human rights instruments, trade agreements, and other relevant legal frameworks concerning health and trade. Through a comprehensive review of case studies and legal analyses, the paper evaluates how international law addresses the challenges posed by health sector liberalization and seeks to safeguard the right to health. Additionally, it considers the role of international organizations, such as the World Health Organization (WHO) and the World Trade Organization (WTO), in balancing trade liberalization objectives with public health imperatives. The analysis highlights the tensions and synergies between economic interests and health rights, offering insights into potential strategies for reconciling these competing priorities. By elucidating the evolving landscape of international legal responses, this paper contributes to the ongoing discourse on achieving equitable access to healthcare while promoting global economic integration.